Optimal production areas of underutilized indigenous crops and their role under climate change: Focus on Bambara groundnut - Nhamo, Luxon; Paterson, Garry; van der Walt, Marjan; Moeletsi, Mokhele; Modi, Albert; Kunz, Richard; Chimonyo, Vimbayi; Masupha, Teboho; Mpandeli, Sylvester; Liphadzi, Stanley; Molwantwa, Jennifer; Mabhaudhi, Tafadzwanashe (Frontiers in Sustainable Food Systems, 2022)
Food demand in Africa continues to outstrip local supply, and the continent currently spends over US35 billion annually on food imports to supplement local deficits. With the advances in agronomy and breeding, commercial crops like maize (Zea mays) and soybean (Glycine max) in the region are under threat from climate change, decreasing rainfall and degraded lands. Unlike commercial crops that are generally adapted from other regions, underutilized indigenous crops are uniquely suited to local environments and are more resilient to climatic variations and tolerant to local pests and diseases. This study, done in Limpopo Province, South Africa, identifies optimal areas for cultivating Bambara groundnuts (Vigna subterannea), an indigenous crop suitable for arid and semi-arid regions. The aim is to promote the production of underutilized indigenous crops at a large scale with fewer resources, while still meeting local demand and reducing the food import budget. Suitability maps are delineated using a multicriteria decision method in a Geographic Information System (GIS). The procedure is important for diversifying farming systems, making them more resilient (to biotic and abiotic stresses and climate change) and more successful at enhancing water, food and nutritional security. With the province's limited water and land resources for agriculture expansion, promoting indigenous underutilized crops is a pathway to reduce water allocated to agriculture, thereby enhancing drought resilience and ensuring water, food and nutritional security. Large tracts of degraded agricultural land deemed unsuitable for adapted crops, and which may require costly land reclamation practices, can be used to cultivate underutilized crops that are adapted to extreme local conditions.